Corporate tax audits: evidence from Malaysia - Isa, Khadijah; Pope, Jeff (World Business Institute, Australia, 2011)
Tax audit, a key feature of the self-assessment system (SAS), may have a significant deterrent effect on taxpayers. Previous studies show that the audit experience may influence taxpayers’ compliance behaviour. Though the SAS has been implemented on companies in Malaysia since 2001, information on the efficacy of tax audit activities conducted by the Inland Revenue Board (IRB), particularly feedback from audited taxpayers, is very limited. Survey data are collected from corporate taxpayers to examine the extent of their audit experience. Findings from the study are predominantly positive and should be beneficial for policy makers, particularly the tax authority, in their effort to review and improve the current tax system.